Combined Adipose Tissue-Derived Mesenchymal Stem Cell Therapy and Rehabilitation in Experimental Stroke - Mu, Jingwei; Bakreen, Abdulhameed; Juntunen, Miia; Korhonen, Paula; Oinonen, Ella; Cui, Lili; Myllyniemi, Mikko; Zhao, Shanshan; Miettinen, Susanna; Jolkkonen, Jukka (Frontiers in Neurology, 2019)
Background/Objective: Stroke is a leading global cause of adult disability. As the population ages as well as suffers co-morbidities, it is expected that the stroke burden will increase further. There are no established safe and effective restorative treatments to facilitate a good functional outcome in stroke patients. Cell-based therapies, which have a wide therapeutic window, might benefit a large percentage of patients, especially if combined with different restorative strategies. In this study, we tested whether the therapeutic effect of human adipose tissue-derived mesenchymal stem cells (ADMSCs) could be further enhanced by rehabilitation in an experimental model of stroke. Methods: Focal cerebral ischemia was induced in adult male Sprague Dawley rats by permanently occluding the distal middle cerebral artery (MCAO). After the intravenous infusion of vehicle (n=46) or ADMSCs (2 x 106) either at 2 (n=37) or 7 (n=7) days after the operation, half of the animals were housed in an enriched environment mimicking rehabilitation. Subsequently, their behavioral recovery was assessed by a neurological score, and performance in the cylinder and sticky label tests during a 42-day behavioral follow-up. At the end of the follow-up, rats were perfused for histology to assess the extent of angiogenesis (RECA-1), gliosis (GFAP) and glial scar formation. Results: No adverse effects were observed during the follow-up. Combined ADMSC therapy and rehabilitation improved forelimb use in the cylinder test in comparison to MCAO controls on post-operative days 21 and 42 (P < 0.01). In the sticky label test, ADMSCs and rehabilitation alone or together, significantly decreased the removal time as compared to MCAO controls on post-operative days 21 and 42. An early initiation of combined therapy seemed to be more effective. Infarct size, measured by MRI on post-operative days 1 and 43, did not differ between the experimental groups. Stereological counting revealed an ischemia-induced increase both in the density of blood vessels and the numbers of glial cells in the perilesional cortex, but there were no differences among MCAO groups. Conclusion: Early delivery of ADMSCs and combined rehabilitation enhanced behavioral recovery in an experimental stroke model. The mechanisms underlying these treatment effects remain unknown.